THEMISTOCLES' TWO AFTERLIVES*. (10th September 2015) - McKechnie, Paul
Abstract : 'All political lives…end in failure', as Enoch Powell said; and Themistocles son of Neocles died twice. His first life ended with his ostracism in the late 470 s, after which he was dead to an Athens enthralled by Cimon; but he would not lie down. This article considers his two afterlives: one which ended about 459 in Magnesia on the Maeander, and the other which commenced in the fifth century but continues to resonate today. The examination, however, will be in reverse order, considering first the Themistocles who at Athens was written into what Tim Whitmarsh would call 'the archive', then drawing inferences from that literary afterlife to comment on Athenian politics in Themistocles' years of ostracism, then exile.